Pengaruh Pembelajaran Kontekstual terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas V SD Negeri 173551 Laguboti Tahun Pembelajaran 2024/2025 - Elfrida Aritonang; Dame Taruli Simamora; Rida Gultom; Oktober Tua Aritonang; Wilson Simanjuntak (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The purpose of this study is to find out the influence of Contextual Learning on the Learning Motivation of Christian Religious Education in grade V of SD Negeri 173551 Laguboti for the 2024/2025 Academic Year. The method used in this study is a quantitative research method with the statistics of the Pre-Experimental The One Shot Case Study. The population is all grade V students of SD Negeri 173551 Laguboti which totals 54 people and a sample of 48 people is determined using the Slovin formula. Data was collected with a questionnaire of 30 items. The results of data analysis showed that there was an influence of Contextual Learning on the Learning Motivation of Christian Religious Education in grade V of SD Negeri 173551 Laguboti for the 2024/2025 Academic Year. The analysis requirements test is t table = 2.021 > t cal = 3.022 > t table = 2.021. It is known that the tcount value is in the area of rejection of H0 and acceptance of Ha, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of Contextual Learning on the Learning Motivation of Christian Religious Education in grade V of SD Negeri 173551 Laguboti for the 2024/2025.